Perceptions of older consumers regarding food packaging as a prerequisite for its improvement: A case study of Polish market. (14th February 2018) - Świda, Jarosław; Halagarda, Michał; Popek, Stanisław
Abstract: In many societies, the scale of demographic change associated with increased longevity has the potential to influence the market for consumer goods. As a result, continuous improvement in packaging design that takes into account the needs of older people should become an important challenge for both packaging producers and product manufacturers. Due to the fact that there is limited research concerning the design of food packaging for older people, the aim of the study was to identify the expectations of this group of consumers in this respect. Milk packaging was selected as a model subject of study. Factors influencing older consumers and their buying patterns when purchasing milk have been thoroughly examined. The research was conducted among people over the age of 60 with the use of three methods: a questionnaire (600 subjects), an in‐depth interview (60 subjects) and eye tracking (30 subjects). The results of the study show that older consumers have specific preferences regarding packaging type and design. When considering milk packaging, for example, they prefer glass bottles, simple graphics and font and subdued colours. They most frequently look for information concerning the product's expiration date, its producer's name and its composition. Eye tracking revealed that the older the consumers are, the more problems with finding expiration date they have. The time required to find such information, however, strongly depends on where exactly the expiration date is printed on the packaging. The preferred place in this case is the top of the bottle. Older consumers identify product's brand with the name of the producer. Moreover, the absence of the term 'ingredients': on the milk packaging oftentimes causes confusion among older people, who are concerned about potential food additive content.